The NAC Transcription Factor SlNAP2 Regulates Leaf Senescence and Fruit Yield in Tomato. Issue 3 (14th May 2018) - Ma, Xuemin; Zhang, Youjun; Turečková, Veronika; Xue, Gang-Ping; Fernie, Alisdair R.; Mueller-Roeber, Bernd; Balazadeh, Salma
Abstract : The abscisic acid-activated NAC transcription factor SlNAP2 controls leaf senescence and fruit yield in tomato. Abstract: Leaf senescence is an essential physiological process in plants that supports the recycling of nitrogen and other nutrients to support the growth of developing organs, including young leaves, seeds, and fruits. Thus, the regulation of senescence is crucial for evolutionary success in wild populations and for increasing yield in crops. Here, we describe the influence of a NAC transcription factor, SlNAP2 ( Solanum lycopersicum NAC-like, activated by Apetala3/Pistillata), that controls both leaf senescence and fruit yield in tomato ( S. lycopersicum ). SlNAP2 expression increases during age-dependent and dark-induced leaf senescence. We demonstrate that SlNAP2 activates SlSAG113 ( S. lycopersicum SENESCENCE-ASSOCIATED GENE113 ), a homolog of Arabidopsis ( Arabidopsis thaliana ) SAG113, chlorophyll degradation genes such as SlSGR1 ( S. lycopersicum senescence-inducible chloroplast stay-green protein 1) and SlPAO ( S. lycopersicum pheide a oxygenase), and other downstream targets by directly binding to their promoters, thereby promoting leaf senescence. Furthermore, SlNAP2 directly controls the expression of genes important for abscisic acid (ABA) biosynthesis, S. lycopersicum 9-cis-epoxycarotenoid dioxygenase 1 ( SlNCED1 ); transport, S. lycopersicum ABC transporter G family member 40 ( SlABCG40 ); and degradation, S. lycopersicum ABA 8′-hydroxylase ( SlCYP707A2 ), indicating that SlNAP2 has a complex role in establishing ABA homeostasis during leaf senescence. Inhibiting SlNAP2 expression in transgenic tomato plants impedes leaf senescence but enhances fruit yield and sugar content likely due to prolonged leaf photosynthesis in aging tomato plants. Our data indicate that SlNAP2 has a central role in controlling leaf senescence and fruit yield in tomato.